Elements of influence : the art of getting others to follow your lead - Bacon, Terry R. (American Management Association, 2012)
It can be found in a smile, a handshake, or a friendly chat. Knowing how to influence others is a crucial element of success. We succeed in business and in life when we influence how others think, feel, and act: getting them to accept our point of view, follow our lead, join our cause, feel our excitement, or buy our products and services. The act of influencing is such a part of our daily lives that we often donÆt even realize when we (or others) are doing it. But to succeed, we need to know how influence worksàand how to use it. Influencing effectively requires adaptability, perceptiveness.